Poly(A)-binding proteins and mRNA localization: who rules the roost?. (27th November 2015) - Gray, Nicola K.; Hrabálková, Lenka; Scanlon, Jessica P.; Smith, Richard W.P.
Abstract : RNA-binding proteins are often multifunctional, interact with a variety of protein partners and display complex localizations within cells. Mammalian cytoplasmic poly(A)-binding proteins (PABPs) are multifunctional RNA-binding proteins that regulate multiple aspects of mRNA translation and stability. Although predominantly diffusely cytoplasmic at steady state, they shuttle through the nucleus and can be localized to a variety of cytoplasmic foci, including those associated with mRNA storage and localized translation. Intriguingly, PABP sub-cellular distribution can alter dramatically in response to cellular stress or viral infection, becoming predominantly nuclear and/or being enriched in induced cytoplasmic foci. However, relatively little is known about the mechanisms that govern this distribution/relocalization and in many cases PABP functions within specific sites remain unclear. Here we discuss the emerging evidence with respect to these questions in mammals.